2011
DOI: 10.1186/1471-2180-11-268
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of filamentation (POF1) protein from Saccharomyces cerevisiae is an ATPase involved in the protein quality control process

Abstract: BackgroundThe gene YCL047C, which has been renamed promoter of filamentation gene (POF1), has recently been described as a cell component involved in yeast filamentous growth. The objective of this work is to understand the molecular and biological function of this gene.ResultsHere, we report that the protein encoded by the POF1 gene, Pof1p, is an ATPase that may be part of the Saccharomyces cerevisiae protein quality control pathway. According to the results, Δpof1 cells showed increased sensitivity to hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…We also examined how POF1 deletion might affect cellular fitness. In line with the observation by Costa et al (21), deleting POF1 in qns1⌬ cells conferred sensitivity to H 2 O 2 , which was partially rescued by supplementing a higher concentration of NR (Fig. 4C).…”
Section: Pof1 Functions As An Nmnat Which Catalyzes the Conversion Osupporting
confidence: 76%
See 2 more Smart Citations
“…We also examined how POF1 deletion might affect cellular fitness. In line with the observation by Costa et al (21), deleting POF1 in qns1⌬ cells conferred sensitivity to H 2 O 2 , which was partially rescued by supplementing a higher concentration of NR (Fig. 4C).…”
Section: Pof1 Functions As An Nmnat Which Catalyzes the Conversion Osupporting
confidence: 76%
“…In yeast, Nma1 and Nma2 have been shown to alleviate proteotoxicity in yeast models of proteinopathies (38). Studies by Costa et al (21) suggested that Pof1 has a role in protein quality control. Their study also showed that pof1⌬ exhibited compromised resistance to oxidative stress, heat shock, and chemicalinduced ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation